6y-8-3y+6=0

Simple and best practice solution for 6y-8-3y+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-8-3y+6=0 equation:


Simplifying
6y + -8 + -3y + 6 = 0

Reorder the terms:
-8 + 6 + 6y + -3y = 0

Combine like terms: -8 + 6 = -2
-2 + 6y + -3y = 0

Combine like terms: 6y + -3y = 3y
-2 + 3y = 0

Solving
-2 + 3y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 3y = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 3y = 0 + 2
3y = 0 + 2

Combine like terms: 0 + 2 = 2
3y = 2

Divide each side by '3'.
y = 0.6666666667

Simplifying
y = 0.6666666667

See similar equations:

| X^3-3x=1095 | | 2w-5=9(w-1) | | 11x-4=4(3x-2) | | xy-x^6y^6=0 | | 0.5x+2x+x+45=150 | | -5(r+9)=-96 | | 37.77=8g+3.85 | | 9x-7=23x-15 | | v+914=-21 | | 11x-4=4(3x+2) | | 15x-9-7=x+5 | | z+15+5z+9=180 | | 3x^2-2x-10=7 | | 6x+7+4x+5=90 | | 3X-16=2X+18 | | x^2+6x-8=3x-7 | | 4d-36-24d=2-16-4d | | 28=-4y+2(y+4) | | 6-2(x-2)=3(x+3)-9 | | 2d+15=27 | | x+5-3+3x-3x+x^2+4+x=35 | | 8c-c-1=9 | | 3(24-x)=6-x | | 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x |

Equations solver categories